Optreden van theatergroep waarschijnlijk voor de Bond van Sociaal-Democratische Vrouwenclubs. Serie van 4 fotos
Optreden van theatergroep waarschijnlijk voor de Bond van Sociaal-Democratische Vrouwenclubs. Serie van 4 fotos.